Comparison of clinical presentation and treatment response among youth with atypical anorexia nervosa and anorexia nervosa - Bek Urban; Kelly Cai; David M. Freestone; Megan Hellner; Cara Bohon; Adam Arsenault; Dori M. Steinberg; Jessica H. Baker (PLoS ONE, 2025)
Objective Atypical anorexia nervosa (AAN) is an eating disorder that shares all symptoms with anorexia nervosa (AN) except “significantly low weight.” Here, we aim to further understand the potential similarities and differences between AN and AAN in a clinical sample of patients receiving family-based treatment (FBT) for AN or AAN. The objectives of this study were to 1) compare clinical presentations among adolescent and young adult patients with AN and AAN; and (2) evaluate and compare treatment response to FBT among these patients. Method Clinical data from 1,438 patients (M = 15.3 years, SD = 2.51) undergoing virtual augmented family-based treatment (FBT) who met research specified criteria for AN or AAN were analyzed. To provide the most robust comparison, four common definitions of AAN identified in previous research were retroactively applied to create comparison groups and assess possible differences in symptom presentation and treatment response. Results The percentage of patients classified as AAN ranged from 20%–81.3% depending on definition. Patients with AAN presented with slightly higher eating disorder and depression symptomatology in half of the definitions. All AAN groups gained weight more slowly throughout treatment; other symptom improvement was similar between groups. Conclusions Results show more similarities than differences in presentation and treatment response among patients with AN and AAN and confirm previous pilot studies showing FBT is effective for AAN. Although currently diagnostically distinct, apparent differences between AN and AAN were not found in this study, suggesting a re-consideration of this diagnostic separation.